Case 3682: The work ‘The White-cheeked Geese: Branta canadensis, B. maxima, B. ‘lawrensis’, B. hutchinsii, B. leucopareia, and B. minima. Taxonomy, ecophysiographic relationships, biogeography, and evolutionary considerations, Volume 1, Eastern taxa; Volume 2, Western taxa, biogeography, and evolutionary considerations’ by Harold C. Hanson: proposed suppression for nomenclatural purposes. - Banks, R C; LeCroy, M; Schodde, R (Bulletin of Zoological Nomenclature, 2015)
The purpose of this application, under Articles 78.1 and 81.1 of the Code, is to suppress for nomenclatural purposes the two-Volume work ‘The White-cheeked geese: Branta canadensis, B. maxima, B. ‘lawrensis’, B. hutchinsii, B. leucopareia, and B. minima, taxonomy, ecophysiographic relationships, biogeography, and evolutionary Considerations,’ by Harold C. Hanson. Reasons for suppression are the work’s many confounded new taxon designations, inappropriately chosen types, inadequately diagnosed new taxa, variable and confused authorships, and a flawed neotype designation. Together they serve as evidence of general nomenclatural dysfunction. If not suppressed, Hanson’s work will destabilise the nomenclature of the Branta canadensis complex.
Keywords: Nomenclature; taxonomy; Aves; Anseriformes; ANATIDAE; White-cheeked Goose; Canada Goose; Branta canadensis; Tundra Goose; Branta hutchinsii